AN ANALYSIS OF CONVERSATIONAL IMPLICATURE FOUND IN THE AMERICAN TV SERIES SUPERNATURAL: SEASON 6 - YONATRI, AQIANA EKA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study was conducted to find out the types of conversational implicature in the American TV Series Supernatural: Season 6. The writer selected Supernatural: Season 6 as the data source because the characters often produced implicature utterances. This research discovered that two types of conversational implicature based on the theory of Grice were used by the characters while having conversations with each other. They produced the conversational implicature by either obeying or flouting the conversational maxims. From the occurrence of all types of conversational implicature, the characters mostly used the particularized conversational implicature because most of the utterances they produced required context to interpret the implied meanings. Context could be the physical context, situational context, the cultural knowledge, the private knowledge of a person’s history, and co-textual context.   Keywords: Conversational Implicature, Maxims, Context